2000
DOI: 10.1210/en.141.9.3397
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Is an Agonist of the Growth Hormone Secretagogue Receptor

Abstract: Growth hormone secretagogues (GHSs) are synthetic compounds that induce GH release in several species, including man. The aim of the current study was to identify hypothalamic GHS receptor (GHS-R) agonists. This led to the discovery of adenosine as a GHS-R agonist. We demonstrate that adenosine as well as the A1 adenosine receptor agonist N6-R-phenylisopropyladenosine (R-PIA) induce calcium responses, with EC50 values of 50 nM and 0.5 nM, respectively, in cells which express recombinant human GHS-R. However, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
4

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 0 publications
1
32
0
4
Order By: Relevance
“…The possibility that CYN-154806 acts on GHS-Rs, however, contrasts with the fact that GHS-Rs exhibit a high binding affinity for GH secretagogue compounds that potently stimulate GH secretion, whereas our results demonstrate an inhibitory action of CYN-154806 on GH release. However, there is also some evidence suggesting the existence of additional GHS-Rs that would not mediate GH-releasing effects of GH secretagogues but, rather, would bind to a putative GHS-R ligand which inhibits GH release [41, 43, 44]. These receptors, therefore, may be those mediating CYN-154806 inhibition of GH secretion in GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that CYN-154806 acts on GHS-Rs, however, contrasts with the fact that GHS-Rs exhibit a high binding affinity for GH secretagogue compounds that potently stimulate GH secretion, whereas our results demonstrate an inhibitory action of CYN-154806 on GH release. However, there is also some evidence suggesting the existence of additional GHS-Rs that would not mediate GH-releasing effects of GH secretagogues but, rather, would bind to a putative GHS-R ligand which inhibits GH release [41, 43, 44]. These receptors, therefore, may be those mediating CYN-154806 inhibition of GH secretion in GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, UAG does not bind GHS-R1a [69, 70, 118]. Adenosine was initially proposed to be a partial agonist for GHS-R1a [119,120,121], but this has been questioned [122, 123]. A series of other molecules apparently unrelated to ghrelin have also been shown to bind GHS-R1a, such as the natural SRIH-like neuropeptide cortistatin, some synthetic SRIH-mimetic octapeptides (octreotide, lanreotide and vapreotide) [124,125,126] and the atypical L-type Ca 2+ channel blocker diltiazem [127].…”
Section: Type 1a Ghs Receptormentioning
confidence: 99%
“…These findings point to an overlapping in the agonist-binding site, as receptor agonism does not require identical disposition at the ligand-binding site [16]. In addition, GHSR-1a appears to show another binding site different from the characterized GHS binding pocket, which was revealed by studies developed with adenosine [17, 18]. Ligand binding and site-directed mutagenesis studies showed that adenosine binds to a binding site different from the one characterized for GHSs and ghrelin [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GHSR-1a appears to show another binding site different from the characterized GHS binding pocket, which was revealed by studies developed with adenosine [17, 18]. Ligand binding and site-directed mutagenesis studies showed that adenosine binds to a binding site different from the one characterized for GHSs and ghrelin [17, 18]. Functionality studies demonstrated that adenosine triggers intracellular calcium rise with a slower temporal dynamic than that observed for GHSs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation